2021
DOI: 10.1016/j.isci.2021.103328
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic vaccine affords full protection to mice against lethal challenge of influenza B virus of both genetic lineages

Abstract: HighlightsThe evolution of influenza B viruses necessitates development of universal vaccines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“… 37–42 , 77 , 78 Here, we found that Uni-1, a mono-specific antibody targeting the universally conserved linear epitope, could induce strong ADCC and in vivo protection, a new observation consistent with our recent vaccine studies showing deletion of the fusion peptide could reduce the ADCC as well as weaken the vaccine efficacy induced by a HA2 vaccine. 27 The ADCC activity, along with neutralizing activities, 25 could collectively contribute to the effective protection of animals from lethal challenges of both IAV and IBV as presented in this short report.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“… 37–42 , 77 , 78 Here, we found that Uni-1, a mono-specific antibody targeting the universally conserved linear epitope, could induce strong ADCC and in vivo protection, a new observation consistent with our recent vaccine studies showing deletion of the fusion peptide could reduce the ADCC as well as weaken the vaccine efficacy induced by a HA2 vaccine. 27 The ADCC activity, along with neutralizing activities, 25 could collectively contribute to the effective protection of animals from lethal challenges of both IAV and IBV as presented in this short report.…”
Section: Discussionmentioning
confidence: 88%
“…Specifically, MDCK cells were infected with several strains of IAV, including H1N1, H3N2, H7N7, and H11N6, and IBV, including B/Victoria (Victoria lineage), B/Brisbane (Victoria lineage), B/Yamagata (Yamagata lineage), and B/Florida (Yamagata lineage) before incubation with Uni-1 and FcγRIV effector cells. 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the ease of administration, intramuscular VLP immunization could serve as an alternative to these methods. A recombinant adenovirus vaccine expressing the synthetic HA2 antigen was shown to be effective against influenza B virus infection, as the vaccine enhanced the live GC B cell percentages in the draining lymph nodes and reduced the lung viral loads in mice [ 49 ]. Although GC B cell populations were assessed in a different organ in our study, notably the lung as it is the primary infection site, the results were similar as significantly incremental changes in GC B cell populations were observed.…”
Section: Discussionmentioning
confidence: 99%